2010
DOI: 10.1111/j.1600-0714.2009.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lathyrism on dentin structure of the rat incisors: a morphometric and scanning electron microscopic investigation

Abstract: These findings indicated a deleterious effect of lathyrism on dentin, with a possible negative impact on developing teeth integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…The number of dentinal tubules ranges from 21,000/mm 2 to 48,000/mm 2 in human dentin, at a position halfway between the pulp and enamel. 6,7,15 In this present study, after brushing with different toothpastes, the number of dentin tubules ranged from 23,160/mm 2 to 30,430/mm 2 . These results are very similar to those of other studies using desensitizing agents on rat teeth and on human dentin.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…The number of dentinal tubules ranges from 21,000/mm 2 to 48,000/mm 2 in human dentin, at a position halfway between the pulp and enamel. 6,7,15 In this present study, after brushing with different toothpastes, the number of dentin tubules ranged from 23,160/mm 2 to 30,430/mm 2 . These results are very similar to those of other studies using desensitizing agents on rat teeth and on human dentin.…”
Section: Discussionmentioning
confidence: 46%
“…The cervical area of the incisors was analyzed because it was more appropriate, due to their greater number of dentinal tubules. [13][14][15] The analysis of dentin permeability in this study showed higher dentin permeability in the DW and FT groups. The SCT, PCT and PNT groups had lower dentin permeability.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…During enamel formation, ameloblasts produce a number of matrix proteins that promote and regulate the mineral deposition of ion in apatite crystals (Nanci et al 1998a, b;Orsini et al 2001Bourd-Boittin et al 2004Massa et al 2006). In enamel matrix, amelogenin is the main protein representing 90% of organic content in enamel matrix, but there are also no amelogenin proteins like proteases and anionic proteins such tuftelin and ameloblastin (Deutsch et al 1995;Sasaky and Shimokawa 1995;Fong et al 1996;Krebsbach et al 1996;El Roubi et al 2010;Kumasaka et al 2010;Sumita et al 2010). Amelogenesis involves amelogenin and enamel organic matrix production, their sequential degradation by the metalloproteinases action, and the following organic matrix mineralization that continues until the enamel maturity, producing a highly mineralized tissue (Deutsch et al 1995;Smith 1998;Delgado et al 2001).…”
mentioning
confidence: 96%
“…Odontogenesis is not well understood in human (El Roubi et al 2010;Kavitha et al 2010;Kumasaka et al 2010;Nandaseana et al 2010;Sumita et al 2010). Enamelysin and amelogenin immunolocalization has been done in mice, rats, and pigs incisors (Caterina et al 2000;Bourd-Boittin et al 2004).…”
mentioning
confidence: 97%